PENGARUH VIRAL MARKETING, PERCEIVED QUALITY DAN BRAND TRUST TERHADAP PURCHASE INTENTION PADA APLIKASI TIKTOK (STUDI PRODUK WARDAH GLASTING LIQUID LIP) - Qudsiyah, Nailuna; Widyastuti (Seminar Nasional Manajemen, 2026)
This study aims to analyze the influence of viral marketing, perceived quality, and brand trust on purchase intention of Wardah Glasting Liquid Lip on the TikTok application. This research uses explanatory research with a quantitative approach. The data analysis method used is multiple linear regression analysis. The data were processed using SPSS 26. The independent variables in this study are viral marketing (X1), perceived quality (X2), and brand trust (X3), while the dependent variable is purchase intention (Y). The sample consists of 200 respondents who are female TikTok users aged 18–24 years and have seen content related to Wardah Glasting Liquid Lip. Data were collected using an online questionnaire through Google Form and processed using SPSS. The results indicate that viral marketing, perceived quality, and brand trust have a positive and significant effect on purchase intention. These findings show that digital marketing strategies through TikTok, positive consumer perceptions of product quality, and consumer trust in the Wardah brand can encourage purchase intention toward Wardah Glasting Liquid Lip.